An Elusive Bullet in the Gastrointestinal Tract: A Rare Case of Bullet Embolism in the Gastrointestinal Tract and a Review of Relevant Literature - Saptarshi Biswas; Catherine Price; Sunil Abrol (Case Reports in Critical Care)
Bullet embolism within the gastrointestinal system is extremely rare. Such bullet injuries are infrequently covered in the general literature, but the surgeon should be aware of the phenomenon. Smaller caliber bullets are more common in civilian gunshot wound (GSW) events. These bullets are able to tumble through the gastrointestinal tract and cause perforation of the intestinal lumen which is small enough to be easily missed. Bullets retained in the abdominal cavity should not be dismissed as fixed and should be carefully monitored to ensure that they do not embolize within the bowel and cause occult lesions during their migration. We present a unique case wherein a bullet caused a minute perforation in the small bowel, before migrating to the distal colon, which resulted in late presentation of sepsis secondary to peritonitis.